Fabrication and Implementation of a Microstrip Antenna for Digital Television Reception at UHF Frequencies - Putri Anjali; Yustini Yustini; Aprinal Adila Asril; Danda Maritsyah Putra (International Journal of Wireless And Multimedia Communications, 2025)
Television broadcasting has evolved from analog to digital technology, utilizing digital modulation and compression to efficiently transmit video, audio, and data signals. Antennas play a crucial role in this technology, with microstrip antennas being particularly notable for their compact size, ease of fabrication, and suitability for integration with other telecommunications equipment. The fabricated antenna measures 200 x 235 mm. By optimizing the Destructure Patch Element and Defected Ground Structure techniques, along with the addition of an Inset Feed, a wider bandwidth can be achieved, allowing for the reception of more digital television channels. At its working frequency, the fabricated antenna achieved a return loss of -36.8 dB, a bandwidth of 218.46 MHz, and a frequency range of 481.83 MHz to 700.29 MHz. The measured Voltage Standing Wave Ratio (VSWR) was 1.02, with a gain of 2.11 dBi at 538 MHz, 2.12 dBi at 546 MHz, 2.27 dBi at 626 MHz, and 2.3 dBi at 642 MHz. The radiation pattern was omnidirectional. Using a Vector Network Analyzer, the fabricated antenna was measured to have a return loss of -18.37 dB and a VSWR of 1.27. Additionally, digital TV broadcast testing was conducted, successfully receiving a strong and clear signal.